The effect of attachment style and level of empathy on intimate partner violence in adolescent romantic relationships - Boxford, Fiona A. (2018)
Perpetration of Intimate Partner Violence (IPV) by adults has been shown to be associated with insecure attachments and lower levels of empathy. However, little to no research has explored these factors within the context of adolescent romantic relationships. A study of 603 adolescents explored: (1) the relationship between attachment and occurrence of IPV; (2) the relationship between empathy and occurrence of IPV; (3) the relationship between empathy and attachment; and (4) the interaction effect for attachment and empathy. Results indicated that, for females, high scores on attachment anxiety and attachment avoidance were associated with increased perpetration and victimisation through IPV. For males, high scores on attachment avoidance were linked to increased victimisation by physical violence. For both males and females, lower scores for empathy were associated with increased perpetration of IPV. For females, lower scores for empathy were associated with increased attachment avoidance whilst, for males, higher scores for empathy were associated with increased attachment anxiety. Finally, for female perpetrators of IPV, the interaction between low empathy and high attachment avoidance was found to be important. Whilst for males who were perpetrators of physical violence, the interaction analysis suggested it was the combination of low empathy and low attachment anxiety and/or low empathy and high attachment avoidance that was important. These findings are mostly consistent with the current literature and have important implications as they highlight the need for gender specific and empathy or attachment based IPV interventions.